Carbon Storage Potential and Economic Valuation in the Arboretum of Forest Area with Special Purpose (KHDTK) Aek Nauli, Indonesia - Ramadhani, Nur; Wicaksono, Rezky Lasekti; Rahmadwiati, Rissa (Department of Forestry, Faculty of Agriculture, University of Lampung, 2025)
Sustainable forest management is expected to significantly contribute to preventing climate change and supporting the achievement of the Forestry and Other Land Use (FOLU) Net Sink 2030. This study aims to determine the potential for biomass storage and carbon and economic valuation in the Arboretum of Forest Area with Special Purpose (KHDTK) Aek Nauli, North Sumatra, Indonesia. This study used systematic sampling with random start as an inventory method. The estimation of above-ground carbon uptake used general allometric equations and benefit transfer methods for the economic value of carbon. This study found 62 species of woody plants with 5 species classified as endangered according to the International Union for Conservation of Nature (IUCN) Red List of Threatened Species, namely Agathis dammara, Dryobalanops aromatica, Tectona grandis, Pinus merkusii and Saurauia bracteosa. There are 734 individuals of woody plants, including 84% in the tree phase and 16% in the pole phase, with dominant species in both phases, namely Pinus merkusii and Schima wallichii. Potential biomass and carbon stocks in the pole phase were 4.76 tons/ha and 2.24 tons/ha, respectively, while in the tree phase were 338.69 tons/ha and 159.19 tons/ha. The total estimated carbon sequestration reached 592.42 tons.CO2e/ha. Carbon stocks’ total potential economic value is IDR 2,578,832,243 (USD 164,100). Therefore, the Arboretum of KHDTK Aek Nauli is considered to have the potential to support the achievement of the FOLU Net Sink 2030 target. It is expected that the potential economic value of carbon can be converted into real value and optimized through a carbon trading scheme to offset greenhouse gas emissions and support the sustainable management of KHDTK Aek Nauli. Keywords: benefit transfer, biomass, carbon trade, climate change mitigation, economic potential